Stability of traveling wave solutions to the initial–boundary value problem for diagonalizable quasilinear hyperbolic systems. (April 2015) - Liu, Jianli; Wei, Fenglun
Abstract: In this paper, we consider the stability of all traveling wave solutions to the mixed initial–boundary value problem for diagonalizable quasilinear hyperbolic system in the domain ( t, x ) | t ≥ 0, x ≥ 0 , using the weighted Glimm functional method. An application is given for the interesting model in particle physics.